(untitled) (Journal of Educational Sciences, 2016)
Мақалада жалпы сұрақтар, шолу сабақтар ұғымы туралы баяндалады On reason theories, generalization - as the result of long steady and productive training, is processof difficult, intensive thinking. Difficult creative process of cerebration - result expedient and in the maximum degree of conscious activity. In this process pupils put theoretical skills into practice, study dialectic unity of the theory and practice, and also do the generalized reasonable conclusions.